Study on Export Performance of Wool in Australia - Soumya, P.; Yeledhalli, R. A. (New Visions in Science and Technology Vol. 7, 2021)
The present study is an attempt to analyse share, growth, instability, country-wise exports and direction of trade of wool from Australia. Compound Annual Growth Rate, Cuddy-Della Valle Index and Markov chain analysis are the tools used for analysing data from 2006 to 2020. Australia is the major wool exporting country in the world with a share of 46.95 per cent in export quantity and 65.89 per cent in export value of total world exports. The growth rate of wool exports from Australia in quantity terms is negative (-2.46% per annum) and the growth rate of exports in terms of value is positive (3.99% per annum). The instability index is low (7.90%) for wool exports in quantity terms and is medium (21.16%) for wool exports in value terms. Among major importers, highest growth rate was observed in wool imports to Republic of Korea both in quantity (4.38%) and value (9.10%) terms. Australia exports major quantity of wool to China and it is most stable importer with retention probability of 90.86%. The other reliable importer is India. Steps should be taken by government to exploit existing markets and explore new markets such as Indonesia.